Human Capital Prospective on Corporate Opportunity Identification - Koutu, Khushboo (2012)
Entrepreneurial activities within firms have been a centre of attraction for researchers in past years. Human capital is yet another unexplored prospective affecting and contributing towards entrepreneurship. To understand how individual operate entrepreneurially within firm, we intend to explore how human capital is developed and how structure and practices in internal and external environment of the firm (in this case focusing on Samsung Electronics Corporation) affects human capital development, management and vice versa. In addition to examining the provided framework we also analyse human capital from innovation prospective. Therefore, the paper contributes towards existing literature in two ways: firstly, we exploring and expanding the current framework of corporate opportunity identification and human capital to incorporate innovation. Secondly we provide evidence to support current research through a case analysis and also provide factors to examine in further research